1989
DOI: 10.1111/j.1365-2273.1989.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal airway resistance and symptoms after functional septoplasty: comparison of findings at 9 months and 9 years

Abstract: Thirty-five patients undergoing a functional septoplasty for nasal obstruction and pathologically high nasal airway resistance were followed up twice, at about 9 months and 9 years postoperatively. The resistance of the preoperatively narrower cavity was reduced at both check-ups, while that of the preoperatively wider cavity, and of the total nose, was lower at the late follow-up than at the early one. Seventy-four per cent of the patients were satisfied with the operation at the first follow-up, and 69% at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 6 publications
3
91
1
5
Order By: Relevance
“…Stewart et al 1 and Gandomi et al 4 have shown that nasal obstruction improves significantly within the first three postoperative months, and that this symptom stabilizes by six months after surgery. Jessen et al 14 concluded that an initial improvement of nasal obstruction in the first months to years after surgery becomes progressively undervalued, especially when other causes of obstruction are present, such as chronic rhinitis and sinusitis 1,4 . In our sample, the improvement was significant between the preoperative period and the 7 th postoperative day, followed by a mild improvement between the 14 th and 30 th postoperative day, which remained constant 60 days after surgery (Chart 1).…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al 1 and Gandomi et al 4 have shown that nasal obstruction improves significantly within the first three postoperative months, and that this symptom stabilizes by six months after surgery. Jessen et al 14 concluded that an initial improvement of nasal obstruction in the first months to years after surgery becomes progressively undervalued, especially when other causes of obstruction are present, such as chronic rhinitis and sinusitis 1,4 . In our sample, the improvement was significant between the preoperative period and the 7 th postoperative day, followed by a mild improvement between the 14 th and 30 th postoperative day, which remained constant 60 days after surgery (Chart 1).…”
Section: Discussionmentioning
confidence: 99%
“…In our study the relief that was gained at one month after the surgery, was maintained throughout the follow up period of 4 months. One study showed that the benefi ts of septal surgery had dropped considerably after 9 years [14], and another study showed that the benefi t is maintained [15]. Another prospective study was done for a follow up period of two and a half years which showed that the probability of having at least a 50% reduction in blockage decreased from 73% to 60% to 41% and then to 27% at 3 months, 6 months, 1 year and two and half hears respectively [16].…”
Section: Discussionmentioning
confidence: 98%
“…However, many studies were retrospective. 2,3 Some of those were also chart reviews, retrieving physician rated outcomes. Patient based outcomes were not assessed much in the past.…”
Section: Discussionmentioning
confidence: 99%